Preeclampsia And Its Relationship With Retinopathy Of Prematurity Newborn In Very Low Birth Weight. Perinatal Maternal National Institute 2013-2014 - Chafloque-Cervantes, Augusto (2016)
Retinopathy of Prematurity (ROP) is a vaso-proliferative retinopathy affecting immature infants whose etiology is stillunknown. Some studies have suggested an association between preeclampsia and this pathology. A study was conducted toshow whether preeclampsia is related to the incidence of retinopathy in preterm infants in the National Maternal and PerinatalInstitute. The retrospective, longitudinal -control comparative cases study involves premature very low birth weight (<1500 g.)And less than 32 weeks, born between January 1, 2013 to December 31, 2014 that met inclusion criteria. 201 patients wereconsidered and they were divided into two groups, one with a history of having been born of preeclamptic mother (studio)and one without this background (control) .Both groups were homogeneous in age, sex, weight. the incidence of ROP in bothgroups were compared, showing some degree of ROP 25 of 97 patients with a history of having been born of preeclampticmother (25,8%) and 34 of 104 patients without a history of being born of preeclamptic mother (32,7%) . It was determinedthat there was no relationship between the incidence of ROP and pre eclamptic mother (OR) 0,71 (95% CI 0,4-1,3). It isconcluded that pre-eclampsia is not a risk factor for developing ROP in premature infants with very low weight but if there isa relationship with the severity of ROP.